2021
DOI: 10.1155/2021/4431907
|View full text |Cite
|
Sign up to set email alerts
|

Was Antiphospholipid Syndrome a Risk Factor of Stroke? A Systemic Review and Meta-Analysis of Cohort Studies

Abstract: Antiphospholipid syndrome (APS) is characterized by thrombosis. This systemic review and meta-analysis was to verify the hypothesis that APS might increase the risk of stroke. Studies were identified after literature searching of PubMed, Embase, and Cochrane. Newcastle-Ottawa Quality Assessment Scale Cohort Studies (NOQAS-C) was used to assess the quality of studies. The pooled effect with 95% confidence interval (95% CI) was calculated by random-effect model. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For example, both CeAD and antiphospholipid syndrome are classified together in the rare cause category. However, antiphospholipid syndrome has been associated with a lifetime increased risk of venous and arterial thrombosis, whereas we have shown that patients with CeAD only have a short-term higher risk of recurrent stroke . Thus, 1 category of the TOAST classification contains multiple causes that are studied together but differ highly in terms of prognosis and appropriate secondary prevention strategies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, both CeAD and antiphospholipid syndrome are classified together in the rare cause category. However, antiphospholipid syndrome has been associated with a lifetime increased risk of venous and arterial thrombosis, whereas we have shown that patients with CeAD only have a short-term higher risk of recurrent stroke . Thus, 1 category of the TOAST classification contains multiple causes that are studied together but differ highly in terms of prognosis and appropriate secondary prevention strategies.…”
Section: Discussionmentioning
confidence: 92%
“…However, antiphospholipid syndrome has been associated with a lifetime increased risk of venous and arterial thrombosis, whereas we have shown that patients with CeAD only have a short-term higher risk of recurrent stroke. 28 , 29 , 30 Thus, 1 category of the TOAST classification contains multiple causes that are studied together but differ highly in terms of prognosis and appropriate secondary prevention strategies. This indicates that if we want to investigate the prognosis on a more individual level for young patients with ischemic stroke, the current cause classification system might not suffice, and we need to identify and study subtypes of causes in more detail.…”
Section: Discussionmentioning
confidence: 99%